El cultivo de la yuca en Panama - Aguilar, J.A. (International Center for Tropical Agriculture, 1991)
In Panama most of the cassava is produced by small farmers on marginal, infertile soils with a low level of technology. One of the main cassava producing areas is Ocu, where Ultisols prevail. The most commonly grown var. is Brasilena, with av. yields of 10-12 t/ha. Production constraints include price fluctuation, quick saturation of traditional markets for fresh roots, and the resulting production surpluses. Research on the crop is carried out by the Instituto de Investigacion Agropecuaria de Panama; objectives of plant breeding are to (1) increase the available genetic variability, (2) select high yielding, stable germplasm adapted to the Panamanian ecosystem, and (3) select genotypes adapted to highly acid soils and prolonged droughts in addition to other genotypes apt for agroindustrial purposes. More than 40 genotypes have been introduced in vitro and over 600 F1 lines in the form of botanical seed. Among the introductions, Dayana performed well with yields of 32 t/ha in observation and preliminary yield trials. Other promising genotypes are Brasilena, Chiru, Gigante, and China Amarilla. The infrastructure necessary for international germplasm exchange exists. Mechanisms to effectively multiply and distribute new var. to farmers should be promoted and developed. (CIAT)